Aportes del enfoque tecnólogico a la arqueología preColombina : pasado y presente de la alfarería en el Valle del Río Cuyes y su región (Andes sur-orientales del Ecuador) - Lara, Catherine, (Access archaeology., 2017)
Located in the Northwest of South America (Ecuador), the Cuyes River Valley acts as a transition corridor between the Andean and Amazon regions. This research attempts to determine the ethnic origin of the pre-Columbian inhabitants of the Cuyes valley through the application of a method of ceramic analysis completely new in the region: the technological approach.